Cost Determinants in the 90-Day Management of Isolated Ankle Fractures at a Large Urban Academic Hospital. Issue 7 (July 2018) - Varacallo, Matthew A.; Mattern, Patrick; Acosta, Jonathan; Toossi, Nader; Denehy, Kevin M.; Harding, Susan P.
Abstract : Objectives: To determine the independent risk factors associated with increasing costs and unplanned hospital readmissions in the 90-day episode of care (EOC) for isolated operative ankle fractures at our institution. Design: Retrospective cohort study. Setting: Level I Trauma Center. Patients: Two hundred ninety-nine patients undergoing open reduction internal fixation for the treatment of an acute, isolated ankle fracture between 2010 and 2015. Intervention: None. Main Outcome Measures: Independent risk factors for increasing 90-day EOC costs and unplanned hospital readmission rates. Results: Orthopaedic (64.9%) and podiatry (35.1%) patients were included. The mean index admission cost was $14, 048.65 ± $5, 797.48. Outpatient cases were significantly cheaper compared to inpatient cases ($10, 164.22 ± $3, 899.61 vs. $15, 942.55 ± $5, 630.85, respectively, P < 0.001). Unplanned readmission rates were 5.4% (16/299) and 6.7% (20/299) at 30 and 90 days, respectively, and were often (13/20, 65.0%) due to surgical site infections. Independent risk factors for unplanned hospital readmissions included treatment by the podiatry service ( P = 0.024) and an American Society of Anesthesiologists score of ≥3 ( P = 0.017). Risk factors for increasing total postdischarge costs included treatment by the podiatry service ( P = 0.011) and male gender ( P = 0.046). Conclusions: Isolated operative ankle fractures are a prime target for EOC cost containment strategy protocols. Our institutional cost analysis study suggests that independent financial clinical risk factors in this treatment cohort includes podiatry as the treating surgical service and patients with an American Society of Anesthesiologists score ≥3, with the former also independently increasing total postdischarge costs in the 90-day EOC. Outpatient procedures were associated with about a one-third reduction in total costs compared to the inpatient subgroup.